The role of TNF superfamily members in T-cell function and diseases - Croft, Michael (2009)
Interactions that occur between several tumour necrosis factor (TNF)–TNF receptors that are expressed by T cells and various other immune and non-immune cell types are central to T-cell function. In this Review, I discuss the biology of four different ligand– receptor interactions — OX40 ligand and OX40, 4-1BB ligand and 4-1BB, CD70 and CD27, and TL1A and death receptor 3 — and their potential to be exploited for therapeutic benefit. Manipulating these interactions can be effective for treating diseases in which T cells have an important role, including inflammatory conditions, autoimmunity and cancer. Here, I explore how blocking or inducing the signalling pathways that are triggered by these different interactions can be an effective way to modulate immune responses.